ANALISIS JARI JARI DAN KEMIRINGAN JALAN TERHADAP KECEPATAN KENDARAAN - Nasir Bumulo; Wawan Rauf (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
Road geometric conditions are one of the key factors influencing the safety and comfort of road users. Inappropriate geometric elements, particularly on horizontal curves, can increase the risk of traffic accidents. This study aims to evaluate the suitability of curve radius and cross slope (superelevation) in relation to vehicle speed on the Trans Sulawesi Road section located in Bakti Village, Pulubala District, Gorontalo Regency. The research employed field surveys and geometric calculation analysis based on the 2021 Guidelines for Intercity Road Geometric Design. The collected data included curve radius, curve angle, superelevation, and the average vehicle speed at six curve segments selected as the research objects. The analysis results indicate that among the six evaluated curves, only one curve with a radius of 109 m satisfies the recommended safety criteria. The remaining five curves have relatively small radii, which may potentially increase the risk of traffic accidents. In addition, one curve was found to have a superelevation value of 8.71%, exceeding the recommended maximum limit of 8%. These findings indicate that several geometric elements of the road segment do not fully comply with the established geometric design standards. Therefore, improvements in road safety are required through geometric design adjustments and the installation of warning signs to enhance the safety and comfort of road users. Keyword: Curve Radius, Road Geometry, Superelevation, Vehicle Speed